KNOWLEDGE MANAGEMENT: STRATEGIC FORESIGHT UNIVERSITY MODE2 - Carruyo, Norcelly; Yusbely, Yusbely; Muñoz, Helmer (Revista Arbitrada Formación Gerencial, 2022)
This article allowed the analysis of knowledge management as a strategic prospective of the university mode 2, under the scenario technique. It uses the quantitative analysis method, framed in the logical positivist paradigm, since the research relies on documentary sources, under a descriptive modality and using the non-experimental transectional or transversal design. The population consisted of four documents and the technique and data collection instrument used is a comparative table where different items were reviewed (Characteristics, management process, transfer strategies, toolbox of strategic foresight and use of tools). Among the conclusions are that the management of knowledge is based on research, which is intimately linked to creativity since to a large extent the results of research is also the creation of knowledge or technology. The actors of the exploration process are those who do the research, consume research and use it pertinently in the development of mode 2 universities.